Penerapan Undang-Undang Perlindungan Konsumen Mengatur Tentang Transaksi Bisnis Dengan Menggunakan Artificial Inteligence - Reynaldi Alfrido Kurniawan; Weny Almoravid Dungga; Mellisa Towadi (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to understand and comprehend the urgency of implementing Artificial Intelligence in service business transactions as well as the application of the Consumer Protection Law in regulating business transactions using Artificial Intelligence. This research was conducted using a type of normative legal research supported by empirical data. In research activities, researchers also use data collection techniques through interviews and documentation. Based on the research that has been carried out, the results show that the implementation of Artificial Intelligence in business transactions provides a number of significant benefits in business. This includes increased operational efficiency, better data analysis, being able to answer messages automatically and the ability to make decisions in a more timely manner. In addition, the application of the Consumer Protection Law in business transactions using Artificial Intelligence is very important to maintain consumer rights and security.